Depression among Females in AL-Sader city, Baghdad, Iraq. - Jasim, Hadeel M.; Ali, Besma M.; Al-Kaseer, Eman A.; AL-Diwan, Jawad (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Literature documented that depression is a sequelae of exposure to wars and widespread violence. In Iraq, high figures of depression were published.Objectives: To report on the prevalence of depression among women in the high crowded area, Al-Sader city, Baghdad.Method: A total of 440 females were included in this study. There were selected randomly from relatives of patients accompanied them in attending to primary health care centers. Beck –Depression Inventory (BDI)-II was used to assess depression. Demographic data were requested, too.Result: The prevalence of depression was 68.4%. Old age women, divorced and widows were determinants of depression. Education and crowding index (socioeconomic status) were not obvious determinants of depression.Conclusion: High prevalence of depression was observed.